2016
DOI: 10.3892/ijo.2016.3607
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol glycan anchor biosynthesis, class X containing complex promotes cancer cell proliferation through suppression of EHD2 and ZIC1, putative tumor suppressors

Abstract: We identified phosphatidylinositol glycan anchor biosynthesis, class X (PIGX), which plays a critical role in the biosynthetic pathway of glycosylphosphatidylinositol (GPI)-anchor motif, to be upregulated highly and frequently in breast cancer cells. Knockdown of PIGX as well as reticulocalbin 1 (RCN1) and reticulocalbin 2 (RCN2), which we found to interact with PIGX and was indicated to regulate calcium-dependent activities, significantly suppressed the growth of breast cancer cells. We also identified PIGX t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Several studies have demonstrated that downregulation of RCN1 in some cancer cells significantly suppresses cell proliferation . Our findings reinforce these observations that RCN1 deletion significantly suppresses PCa cell viability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have demonstrated that downregulation of RCN1 in some cancer cells significantly suppresses cell proliferation . Our findings reinforce these observations that RCN1 deletion significantly suppresses PCa cell viability.…”
Section: Discussionsupporting
confidence: 91%
“…These observations suggest that RCN1 may not be directly correlated with the metastatic potential of PCa. High RCN1 and RCN2 expression has recently been associated with shorter recurrence‐free survival in breast cancer patients . Therefore, the contribution of RCN1 to carcinogenesis and cancer progression may be dependent on the cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Subtypes of ZICs were reported to play distinct roles in organism development [25], and were also reported to be closely associated with cancers. ZIC1 expression was shown to be increased in gastric cancers [26], and ZIC1 methylation was considered as a more promising biomarker of cervical cancers, head and neck squamous cell carcinomas and breast cancers [27][28][29]. Furthermore, Lu et al demonstrated that ZIC2 promoted hepatocellular tumor growth and metastasis [30].…”
Section: Discussionmentioning
confidence: 99%
“…ZIC1 (Zinc finger of the cerebellum) is found to be highly suppressed via hypermethylation in colorectal cancer and is known to be a tumor suppressor Gan et al 97 . However, in breast cancer cases as Nakakido et al 98 show, the expression of ZIC1 is found to be regulated by the knockdown of PIGX as well as RCN1 (reticulocalbin 1) and (reticulocalbin 2) RCN2. Thus upregulation or overexpression of RCN2 negatively regulates ZIC1 for cancer proliferation.…”
Section: Dicationmentioning
confidence: 97%
“…However, in breast cancer cases as Nakakido et al 98 show, the expression of ZIC1 is found to be regulated by the knockdown of PIGX as well as RCN1 (reticulocalbin 1) and (reticulocalbin 2) RCN2. Thus upregulation or overexpression of RCN2 negatively regulates ZIC1 for cancer proliferation.…”
Section: Dicationmentioning
confidence: 97%